Pengaruh Tata Kelola Perusahaan, Pelaporan Keberlanjutan, dan Koneksi Politik terhadap Penghindaran Pajak - Ryan Yusuf Hardiono; Faisal Reza Mahendra; Muhammad Irvan Paleva; Ice Nasyrah Noor (Syntax Corporation Indonesia, 2024)
The purpose of this study is to examine the effect of corporate governance, sustainability reporting, and political connections on tax avoidance practices. The data used in the study involves data derived from the financial statements of companies in the infrastructure sector listed on the Indonesia Stock Exchange for the period 2020 to 2022. Information is obtained through the page www.idx.co.id and from the website of each company. The method applied in the research is quantitative method, using purposive sampling data collection technique. While the number of samples selected for this study was 30 observations. The research findings show that corporate governance represented by independent commissioners and audit committees, as well as sustainability reporting has a negative effect on tax avoidance.